Effect of Extraction Methods on Polyphenols, Flavonoids, Mineral Elements, and Biological Activities of Essential Oil and Extracts of Mentha pulegium L - Messaoudi, Mohammed; Rebiai, Abdelkrim; Sawicka, Barbara; Atanassova, Maria; Ouakouak, Hamza; Larkem, Imane; Egbuna, Chukwuebuka (MDPI, 2021)
ur study evaluated the in vitro antioxidant properties, antibacterial and antifungal activities, anti-inflammatory properties, and chemical composition of the essential oils (EOs), total phenol, and total flavonoid of wild Mentha pulegium L. This study also determined the mineral (nutritional and toxic) elements in the plant. The EOs were extracted using three techniques—hydro distillation (HD), steam distillation (SD), and microwave-assisted distillation (MAD)—and were analyzed using chromatography coupled with flame ionization (GC-FID) and gas chromatography attached with mass spectrometry detector (GC-MS). The antioxidant effects of the EOs were tested with 2,2-diphenyl-1-picrylhydrazyl (DPPH) and ABTS (2,2’-azino-bis(3-ethylbenzothiazoline-6-sulfonic acid), while the antibacterial and antifungal activities of the EO and methanolic extract were tested using Staphylococcus aureus, Bacillus subtilis, Pseudomonas aeruginosa, Escherichia coli, and Candida albicans. Twenty-six compounds were identified in the essential oil, representing 97.73% of the total oil, with 0.202% yield. The major components were pulegone (74.81%), menthone (13.01%) and piperitone (3.82%). Twenty-one elements, including macro- and micro-elements (Ba, Br, Ca, Cl, Co, Cr, Cs, Eu, Fe, K, Mg, Mn, Mo, Na, Rb, Sb, Sc, Sr, Th, U and Zn), were detected using neutron activation analysis (INAA) and inductively coupled plasma optical emission spectrometry (ICP-OES), with the concentration of mineral element close to the FAO recommendation. The results show that the EOs and extracts from Mentha pulegium L. had significant antimicrobial activities against the microorganisms, including five human pathogenic bacteria, one yeast (Candida albicans), and one phytopathogenic fungi. The in vivo anti-inflammatory activities of the leaf extracts were confirmed. The results indicate that the EOs and extracts from Mentha pulegium L. have promising applications in the pharmaceutical industries, clinical applications, and in medical research.
Article
Keywords: Mentha pulegium; essential oils; mineral; total phenol; biological activity; antimicrobial properties